Local Union Democracy: In Search of Criteria - Anderson, John (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1979)
A vast number of criteria have been proposed as indicators of union democracy. Unfortunately, little agreement exists on the relative importance of those criteria. This article examines the interrelationships between several major components of union democracy: participation, electoral control, leadership responsiveness, and union control structure. Based on the results an integrated approach to union democracy is proposed.